2011
DOI: 10.4103/0974-777x.91052
|View full text |Cite
|
Sign up to set email alerts
|

Etiological study of fever of unknown origin in patients admitted to medicine ward of a teaching hospital of Eastern India

Abstract: Background:In a developing country, infectious disease remains the most important cause of fever, but the noncommunicable diseases, like malignancy, are fast becoming important differential diagnoses. An important clinical problem is the cases labeled as fever of unknown origin (FUO), which often evade diagnosis.Objective:The present study was undertaken to find the cause of FUO in a tertiary care hospital of eastern India.Materials and Methods:This is a prospective study of inpatients, with regard to both cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 6 publications
(6 reference statements)
0
20
0
Order By: Relevance
“…17,21,2931 Unlike most outpatient studies, none of the inpatient studies were designed to evaluate the diagnostic accuracy of CRP for pulmonary TB; 17,21,2931 in general, these studies were judged to have higher and/or unclear risk of bias and greater concerns for applicability for all domains. Only two studies reported enrolling a consecutive or random sample of patients, 17,21 while the remaining studies did not provide sufficient information to determine the patient selection method.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…17,21,2931 Unlike most outpatient studies, none of the inpatient studies were designed to evaluate the diagnostic accuracy of CRP for pulmonary TB; 17,21,2931 in general, these studies were judged to have higher and/or unclear risk of bias and greater concerns for applicability for all domains. Only two studies reported enrolling a consecutive or random sample of patients, 17,21 while the remaining studies did not provide sufficient information to determine the patient selection method.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported enrolling a consecutive or random sample of patients, 17,21 while the remaining studies did not provide sufficient information to determine the patient selection method. 2931 Most studies did not enroll a representative spectrum of patients. 17,2931 Although all studies used culture as the reference standard for TB, 17,21,2931 none of the studies explicitly stated that researchers assessing TB status were blinded to CRP results and only one study reported the time elapsed between blood collection for CRP testing and specimen collection for TB evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations